НАЛОГОВАЯ НАГРУЗКА КАК ЭКОНОМИЧЕСКИЙ ПОКАЗАТЕЛЬ, ХАРАКТЕРИЗУЮЩИЙ НАЛОГОВУЮ СИСТЕМУ ГОСУДАРСТВА (Journal of Economic Research & Business Administration, 2015)
In article various techniques of definition of tax loading and degree of influence of these techniques on definition of a uniform methodological basis of calculation of tax burden are considered.